Determinants of Voter Perception towards E-Voting System in India: A Confirmatory Factor Analysis - Vij, Namrata; Saha, Shantanu (Indian Journal of Computer Science, 2017)
The aim of the present study was to examine voters’ perception of e-voting system in India. Here, e-voting system refers to an online voting anywhere in the country by voters in public elections. The goals of an e-voting system is to increase voter participation and relieve congestion at polling stations on election day. E-voting is similar to "no-excuse" absentee voting. E-voting system increases the participation of voters in India. The main reason for conducting the research was to know the perception of voters towards acceptability of digital India campaign led by the Government of India. Responses were gathered through 276 prospective travelers having a transferable job and may not be present in their city at voting time. Computer aided qualitative data analysis software (CAQDAS) was used to explore the factors through content analysis and the same was empirically experimented by using EFA and CFA through SPSS and AMOS software. The finding suggested that new factors conveyed the perceptions of voters towards Â accepting e-voting system concepts in India. Further, government organizations as well as voters may perhaps benefit from the research outcome. E-voting may be thought of as a solution of replacing the ballet box and it can lead to transformation of India from a developing into a developed nation.